ANALISIS KINERJA KEUANGAN MENGGUNAKAN ECONOMIC VALUE ADDED (EVA) DAN MARKET VALUE ADDED (MVA) PADA BANK BUMN GO PUBLIC PERIODE 2014-2019 - Khairil Akbar; Amiruddin Amiruddin; Agung Frima Nugroho (Politeknik Negeri Samarinda, 2021)
The purpose of the paper is to determine financial performance using Economic Value Added (EVA) and Market Value Added (MVA) in the 2014-2019 Bank Of BUMN Go Public . The method used in this study is a Quantitative Method, using Economic Value Added (EVA) and Market Value Added (MVA) analysis tools. The results of this study that by using Economic Value Added (EVA) and Market Value Added (MVA) the result at PT Bank Mandiri (Persero) Tbk, PT Bank Negara Indonesia (Persero) Tbk, and PT Bank Rakyat Indonesia (Persero) Tbk worth positive on EVA and also MVA or EVA> 0 and MVA> 0, this shows that the BUMN Go Public Company has succeeded in creating economic value-added companies and also market added value.